Public Service Provisions for Land Resource Planning - Kitjarak, Teeraphat; Pathak, Shubham; Qi, Xinlin; Boripis, Thussaneeya (Ital Publication, 2025)
This study explored the intricate nexus between public service provision and land use planning, specifically focusing on the conservation of local plant species in Tambon Khao Phanom, Amphoe Khao Phanom, Krabi Province. The research aimed to explore, understand, and analyze Thailand's land use resources, planning, and implementation. This study employed a multi-method research approach to gather an exhaustive set of data and insights. The researcher collected data from documentation research and secondary data sources in this research study. Based on the grounded theory, this research adopts the triangulation method. The data analysis was done using the 5P model and strengths, weaknesses, threats, and opportunities. This multidisciplinary approach integrates the one-map method with the Sustainable Development Goals (SDGs). The findings depict the lack of adequate implementation of government policies and awareness among the landholders, which are required for sustainable community development. This study underscores the critical synergy between public service delivery and land use planning, highlighting their collective potential to advance community well-being and sustainable development. Doi: 10.28991/ESJ-2025-09-01-021 Full Text: PDF